2015
DOI: 10.1038/srep12702
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed N2O formation during NH3 selective catalytic reduction using vanadium on zeolitic microporous TiO2

Abstract: Emission of N2O from mobile and off-road engine is now being currently regulated because of its high impact compared to that of CO2, thereby implying that N2O formation from the exhaust gas after-treatment system should be suppressed. Selective catalytic reduction using vanadium supported TiO2 catalyst in mobile and off-road engine has been considered to be major source for N2O emission in the system. Here we have demonstrated that vanadium catalyst supported on zeolitic microporous TiO2 obtained from the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…These microporous TiO 2 particles have a fine pore structure (pore size of less than 1 nm, similar to zeolite), which seems to be formed by Li + intercalation. Details of the synthetic method for microporous TiO 2 have been reported previously . Before Mn impregnation, it was confirmed that there was no residual Li ion on the as-synthesized microporous TiO 2 from the ICP-AES results.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…These microporous TiO 2 particles have a fine pore structure (pore size of less than 1 nm, similar to zeolite), which seems to be formed by Li + intercalation. Details of the synthetic method for microporous TiO 2 have been reported previously . Before Mn impregnation, it was confirmed that there was no residual Li ion on the as-synthesized microporous TiO 2 from the ICP-AES results.…”
Section: Resultsmentioning
confidence: 58%
“…Microporous structure inside TiO 2 particle was made using the hydrothermal synthesis method as previously reported. 21 In a typical synthesis, 70.5 g of lithium hydroxide (Aldrich, >98%) and 6.4 g of anatase titanium(IV) oxide (Aldrich, >99.8%) were mixed in 141 mL of deionized H 2 O and vigorously stirred at room temperature for 2 h. The mixture was transferred to a 200 mL Teflon cup and placed in a stainless-steel autoclave. The autoclave was then heated at 127 °C for 30 h in a rotating oven with a speed of 17 rpm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vanadium oxide supported on anatase titania catalyst (VO x /TiO 2 ) is active for various reactions including selective oxidation or reduction. It has been well known as a conventional catalyst used in the selective catalytic reduction (SCR) process, which selectively reduces harmful NO x with NH 3 in lean conditions. Many studies have been performed to investigate structure–activity relationship in VO x /TiO 2 catalyst, where it is widely accepted that the degree of polymerization of vanadia on TiO 2 is a key factor that determines the activity or selectivity in the reaction. , …”
Section: Introductionmentioning
confidence: 99%
“…water. 1 g of a microporous TiO 2 support (Lab made) 33 was added into the precursor solution and stirred for 30 min. The solution with microporous TiO 2 support was dehydrated by using a rotary evaporator and completely dried at 105 °C overnight.…”
Section: Methodsmentioning
confidence: 99%